Knowledge, attitudes, and behaviors of teachers and students toward sustainable development of Pili (Canarium ovatum) - Funa, Aaron Aytona; Gabay, Renz Alvin Emberga; Ibardaloza, Rosel T.; Limjap, Auxencia Alarcon (Jurnal Cakrawala Pendidikan, 2022)
The urgent call by UNESCO to scale up interventions for the achievement of sustainable development goals motivated this study to assess the level and association of teachers’ (n =107) and students’ (n = 342) knowledge, attitudes, and behaviors (KAB) regarding education for sustainable development, focusing on Pili (Canarium ovatum). This is a subset of a larger project that involves Pili to contextualize learning and instructional materials. The researchers used a descriptive cross-sectional survey approach and distributed a questionnaire through Google Forms. KAB levels were categorized into poor, moderate, and high using descriptive data analysis and determined their association with one another using Pearson’s Chi-square. The findings indicate that, although the associations among the KAB of teachers are distinct from those of the students, they both perceived that possessing favorable knowledge and attitudes are insufficient to generate positive behaviors. Thus, efforts to increase teachers’ and students’ motivation and involvement and to help them carry out favorable behaviors toward sustainable development are imperative. Given this, identifying the barriers to converting knowledge and attitudes into behaviors and considering the factors that involve the association of KAB in promoting sustainable development, particularly in education, are recommended.